2018
DOI: 10.1530/rep-17-0456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cariporide on ram sperm pH regulation and motility: possible role of NHE1

Abstract: Sperm motility, a feature essential for fertilization, is influenced by intracellular pH (pH) homeostasis. Several mechanisms are involved in pH regulation, among which sodium-hydrogen exchangers (NHEs), a family of integral transmembrane proteins that catalyze the exchange of Na for H across lipid bilayers. A preliminary characterization of NHE activity and kinetic parameters, followed by analysis of the expression and localization of the protein in ram spermatozoa was performed. NHE activity showed an appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
0
20
1
Order By: Relevance
“…As the main transporters for eliminating the cytosolic protons, six isoforms of NHEs: NHE1 [31][32][33], NHE5 [34], NHE8 [35], sNHE [36,37], NHA1 [38], and NHA2 [39] had been reported to be expressed in sperm. However, which NHE is the determinant modulator for the activation of KSper and CatSper in murine sperm remained ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…As the main transporters for eliminating the cytosolic protons, six isoforms of NHEs: NHE1 [31][32][33], NHE5 [34], NHE8 [35], sNHE [36,37], NHA1 [38], and NHA2 [39] had been reported to be expressed in sperm. However, which NHE is the determinant modulator for the activation of KSper and CatSper in murine sperm remained ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that caspase 3 plays an important role in apoptosis in the endoplasmic reticulum [8]. In this study, the GSVs discarded during CABG were collected, and the vein was preserved according to the condition of each group.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous research using patch-clamping in mouse sperm demonstrated that NHE channels are functionally coupled to the CatSper ones [ 4 , 11 ]. Furthermore, recent studies reported that sNHE in humans [ 17 ] and NHE1 in sheep [ 18 ] are implicated in the regulation of sperm motility. Since not only does the process through which a spermatozoon acquires their capacity to fertilize an oocyte entail changes in sperm kinematics but also in plasma membrane permeability, intracellular calcium levels, mitochondrial activity, and acrosome integrity, the objective of the present study was to determine the physiological relevance of NHE channels in the sperm ability to elicit in vitro capacitation and progesterone-induced acrosome exocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Since not only does the process through which a spermatozoon acquires their capacity to fertilize an oocyte entail changes in sperm kinematics but also in plasma membrane permeability, intracellular calcium levels, mitochondrial activity, and acrosome integrity, the objective of the present study was to determine the physiological relevance of NHE channels in the sperm ability to elicit in vitro capacitation and progesterone-induced acrosome exocytosis. These assays were based on the pharmacological blockage of NHEs channels using a specific inhibitor (5-(N,N-dimethyl)-amiloride; DMA) at different concentrations [ 4 , 18 ]. DMA induces the total blockage of NHE1 and NHE2 isoforms and the partial blockage of NHE5; in contrast, NHE3 and NHE4 are amiloride-resistant isoforms (reviewed in [ 14 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation